Coastal Louisiana Risk Assessment Model Technical Description and 2012 Coastal Master Plan Analysis Results - Fischbach, Jordan R. (RAND Corporation, 2012)
Describes the Coastal Louisiana Risk Assessment (CLARA) model developed by RAND to estimate flood depths and damage that occurs as a result of major storms in Louisiana's coastal region. CLARA made it possible to evaluate potential projects for inclusion in the Louisiana's 2012 Coastal Master Plan on the basis of how well they reduce flood damage over the next fifty years. Also describes damage reduction provided by the final Master Plan.